Metabolism of mineral‐sorbed organic matter and microbial lifestyles in fluvial ecosystems. Issue 4 (19th February 2016) - Hunter, William Ross; Niederdorfer, Robert; Gernand, Anna; Veuger, Bart; Prommer, Judith; Mooshammer, Maria; Wanek, Wolfgang; Battin, Tom J
Abstract: In fluvial ecosystems mineral erosion, carbon (C), and nitrogen (N) fluxes are linked via organomineral complexation, where dissolved organic molecules bind to mineral surfaces. Biofilms and suspended aggregates represent major aquatic microbial lifestyles whose relative importance changes predictably through fluvial networks. We tested how organomineral sorption affects aquatic microbial metabolism, using organomineral particles containing a mix of 13 C, 15 N‐labeled amino acids. We traced 13 C and 15 N retention within biofilm and suspended aggregate biomass and its mineralization. Organomineral complexation restricted C and N retention within biofilms and aggregates and also their mineralization. This reduced the efficiency with which biofilms mineralize C and N by 30% and 6%. By contrast, organominerals reduced the C and N mineralization efficiency of suspended aggregates by 41% and 93%. Our findings show how organomineral complexation affects microbial C:N stoichiometry, potentially altering the biogeochemical fate of C and N within fluvial ecosystems. Key Points: Mineral sorption restricts the uptake and mineralization of organic matter by aquatic microbes Biofilms and suspended microbial aggregates respond differently to mineral‐bound organic matter Organomineral sorption alters the stoichiometry of microbial carbon and nitrogen cycling